APLIKASI KULIT LABU Curcubitaeae sp. SEBAGAI SUMBER STIMULASI UNTUK PROSES NITRIFIKASI DAN DENITRIFIKASI DI LINGKUNGAN BUDIDAYA UDANG VANAME (Litopenaeus vannamei) - Yuni Puji Hastuti; Muhammad Saifuddin; Eddy Supriyono; Wildan Nurussalam; Dudi Lesmana; Andri Hendriana; Ima Kusumanti (Universitas Djuanda, 2022)
Aplication of pumpkin skin flour Curcubitae sp. to improve of the water quality performance and support shrimp Litopenaeus vannamei growth, it necessary to do an analysis. Pumpkin skin Curcubitae sp. as a source of stimulants needed by bacteria to survive in the nitrification denitrification processes in aquaculture as an alternative to environmental friendly with bioremediation system evaluation. Its mesophilic nature and a organic ions source for bacterial growth. Pumpkin skin can support the growth and activity of nitrifying denitrifying bacteria in the environment. This study aims to determine the best of dose of pumpkin skin as a biostimulator of nitrifying denitrifying bacteria growth. The treatments used were pumpkin doses of 0%, 2%, 4%, 6% for 20 L culture water. Giving pumpkin flour can improve the performance of abundance and activity of nitrification denitrification bacteria. The activity of nitrifying bacteria can be seen from the presence of ammonia value which is relatively more stable compared to other treatments. The best oxidation of ammonia in 6%, and reduction nitrite in the 4% treatments. The treatment of 4% was effective in maintenance for 30 days which could maintain the stability of water quality and increase the growth of vaname shrimp.